Postpartum Depression and Exclusive Breastfeeding In Infants Aged 0-5 Months Old - Ishmatika, Enka Nur; Wijayati, Azmi (Persatuan Dosen Kesehatan Masyarakat, 2025)
Exclusive breastfeeding is the most essential period for the early life of an infant. Various factors influence the mother’s initiation and behavior of breastfeeding. Including postpartum depression as maternal mental health issue. This study aims to analyze the relationship of postpartum depression with exclusively breastfeeding in infants (0-5 months) in Indonesia. This research is quantitative using secondary data from the National Health Research (Indonesian Basic Health Research) with cross sectional research methods and were processed in 2020. The sample of this study was women aged 15-49 years with infants aged 0-5 months in Indonesia, totaling 2332 people. Bivariate analysis with Chi Square test was found that the relationship of postpartum depression towards exclusive breastfeeding was not significant with p value 0.911 (OR 0.946, 95% CI : 0.355-2.522). While the multivariate test results obtained maternal age, work status, residence and early initiation breastfeeding status (p value <0.05) with each OR respectively 0.770 (95% CI 0.588-1.008), 0.766 (95% CI 0.602-0.976), 0.671 (95% CI 0.537-0.837), and 0.568 (95% CI 0.443-0.728) as the confounding variables. This study concludes that a need to evaluate the early initiation breastfeeding, exclusive breastfeeding program and maternal mental health problems screening during the postpartum period.Keywords: postpartum; breastfeeding; ages; depression; mental